2020
DOI: 10.15446/rcciquifa.v49n1.87033
|View full text |Cite
|
Sign up to set email alerts
|

Composición de ácidos grasos de extractos etéreos de Bryophyllum pinnatum Lam., Ficus exasperata Vahl., Gossypium herbaceum Linn. y Hilleria latifolia (Lam.) H. Walt

Abstract: Actualmente, existe un creciente interés en identificar fuentes alternativas de ácidos grasos debido a la creciente demanda actual de productos botánicos ricos en aceite en aplicaciones industriales. El objetivo principal de este trabajo fue identificar las composiciones de ácidos grasos de extractos de éter de hojas secas de Bryophyllum pinnatum Lam., Ficus exasperata Vahl., Gossypium herbaceum Linn. y Hilleria latifolia (Lam.) H. Walt. Los ácidos grasos fueron analizados por cromatografía de gases con detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…However, there might be possible limitations to its effectiveness in human nutrition due to the fact that it could cause cardiac poisoning in grazing animals (Reppas, 1995 ). The phytochemical profiling of aqueous extract of the leaf of B. pinnatum revealed that it contains terpenoids, alkaloids, lipids, steroids, fatty acids, bufadienolides, phenolics, and flavonoids (Kamboj & Saluja, 2009;Oso, 2020). These phytochemicals are known to contribute immensely to the antioxidant properties of natural materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, there might be possible limitations to its effectiveness in human nutrition due to the fact that it could cause cardiac poisoning in grazing animals (Reppas, 1995 ). The phytochemical profiling of aqueous extract of the leaf of B. pinnatum revealed that it contains terpenoids, alkaloids, lipids, steroids, fatty acids, bufadienolides, phenolics, and flavonoids (Kamboj & Saluja, 2009;Oso, 2020). These phytochemicals are known to contribute immensely to the antioxidant properties of natural materials.…”
Section: Introductionmentioning
confidence: 99%